Lack of Exposure to Mycobacterium Bovis and Mycobacterium Avium Subsp. Paratuberculosis in Chilean Cervids, and Evidence of a New Mycobacterium-Like Sequence - Moreira-Arce, D (Wildlife Disease Association, Inc., 2022)
Screening of serum and fecal samples from huemul (Hippocamelus bisulcus) and pudu (Pudu puda) from southern Chile for Mycobacte-rium bovis and Mycobacterium avium paratuber-culosis (MAP) found all but four samples Mycobacterium-negative. The positive sequences showed only 92–93% similarity with MAP and were from remote Isla Riesco populations. © Wildlife Disease Association 2022.